Nilai-Nilai Pendidikan Akhlak Dalam Al-Qur’an - Mardiah Astuti; Herlina Herlina; Ibrahim Ibrahim; Della Yulanda; Tria Wahyuni; Fenda Resi; Devi Rahma (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The values of moral education are discussed in the Qur'an in this article. This study uses qualitative methodologies that accurately capture the ideals of moral education contained in the Qur'an, especially those used in educational contexts. In this study, there were 100 children and 4 teachers spread across South Sumatra who became informants. In accordance with the research criteria, information was collected using informant interviews and observation methods. Through the use of Google Form, observations and interviews are conducted to analyze data with a qualitative approach, which will make it easier to understand research findings on the principles of moral education. To study the results of this investigation, in particular: In the beginning, in the midst of a time where technology and information are developing rapidly, we can strengthen the values of moral education by using techniques of (1) example, (2) training and habituation, (3) storytelling methods, and (4) recitation activities. Lack of adherence to the teachings of the Qur'an in adolescent moral education will have three negative effects: (1) arbitrary adolescent morals; (2) lack of understanding of what is meant by politeness and civility; and (3) the inability to tolerate the opinions of others. There are three main obstacles that stop people from following moral principles. In fact, in order for good moral beliefs to become a daily routine, they must first be represented at home. Fourth, in the millennial era, parents are the main factor that influences how a child develops morals, and the best way to instill good morals in children is that parents must live by example by acting morally upright in front of their children and grandchildren. If parents behave well, good morals will then develop by themselves in children.